Early Determination of the Periodontal Domain by the Wnt-Antagonist Frzb/Sfrp3 - Mitsiadis, Thimios A.; Pagella, Pierfrancesco; Cantù, Claudio (Frontiers in Physiology, 2017)
Odontogenesis results from the continuous and reciprocal interaction between cells of the oral epithelium and cranial neural crest-derived mesenchyme. The canonical Wnt signaling pathway plays a fundamental role in mediating these interactions from the earliest stages of tooth development. Here we analyze by in situ hybridization the expression patterns of the extracellular Wnt antagonist Frzb/Sfrp3. Although Frzb is expressed in dental mesenchymal cells from the earliest stages of odontogenesis, its expression is absent from a tiny population of mesenchymal cells immediately adjacent to the invaginating dental epithelium. Cell proliferation studies using BrdU showed that the Frzb expressing and Frzb non-expressing cell populations display different proliferative behavior during the initial stages of odontogenesis. DiI-mediated cell-fate tracing studies demonstrated that the Frzb expressing cells contribute to the formation of the dental follicle, the future periodontium. In contrast, the Frzb non-expressing cells give rise to the dental pulp. The present results indicate that Frzb is discriminating the presumptive periodontal territory from the rest of the dental mesenchyme from the very beginning of odontogenesis, where it might act as a barrier for the diffusion of Wnt molecules thus regulating the activation of Wnt-dependent transcription within dental tissues.